PENERAPAN PEMBELAJARAN SECARA OFFLINE DI TENGAH PANDEMI COVID -19 DI SMP BABUSSALAM PEKANBARU - Adiella Zakky Juneid; Miftahul Farhani Isty; Syafrizal Syafrizal; Zulhelmi Zulhelmi; Dina Syaflita (JURNAL MANAJEMEN PENDIDIKAN, 2022)
The Covid-19 outbreak has hampered all human activities, one of which is in learning activities. The Covid-19 outbreak that has lasted for a long time has forced the government to make a new policy, namely the new normal policy. This policy causes people to be able to do activities outside their homes but still maintain a distance, wear masks and always wash their hands. Even so, many schools continue to apply bold learning to prevent the transmission of Covid-19. However, the Pekanbaru Babussalam Middle School starting from the odd semester of 2020/2021 applies offline or face-to-face learning. This research is qualitative in nature to see the effectiveness of offline learning that takes place at Babussalam Junior High School Pekanbaru. Learning at the Pekanbaru Babussalam Middle School is carried out through several stages with the aim of not spreading COVID-19. The results of this study showed that the application of offline learning at Babussalam Junior High School Pekanbaru in the midst of the COVID-19 pandemic went well.